Fighting fascism : the British left and the rise of fascism, 1919-39 - Hodgson, Keith (Manchester University Press ; Distributed in USA by Palgrave Macmillan, 2010)
In the years between the two world wars, fascism triumphed in Italy, Germany, Spain and elsewhere, coming to power after intense struggles with the labour movements of those countries. This book analyses the way in which the British left responded to this new challenge.